Murbeckiella is dead, long live Oreophyton: origin and systematics of tribe Oreophytoneae (Brassicaceae) - Walden, Nora; Mansion, Guilhem; Schnorf, Hektor; Koch, Marcus; Guggisberg, Alessia (Annals of botany, 2025)
The small genus Murbeckiella from the Brassicaceae family underwent manifold taxonomic changes reflecting morphological uncertainties, but also unusual biogeographical distribution patterns ranging from Spain and northern Africa to Caucasus. Close relationships with Oreophyton have been proposed, and both genera have been placed in the orphan tribe Oreophytoneae. We explore phylogenetic relationships to unravel and revise present-day taxonomic treatments, propose a biogeographical framework and contribute to our understanding of the local endemic Murbeckiella omissa from France.To infer general phylogenetic patterns, short-read whole-genome sequencing (WGS) data were mapped to a 1000 nuclear gene target dataset. In addition, divergence time estimates were inferred from plastome coding sequences. Finally, the recently introduced Paralog PhyloGenomics (PPG) approach was tested to detect putative hybrids and resolve reticulate evolutionary patterns at the polyploid level.The PPG concept resolved phylogenetic relationships among diploids and polyploids successfully. Murbeckiella appeared poly- and paraphyletic and the majority of species have been taxonomically integrated into a newly defined genus, Oreophyton. One single species, Murbeckiella sousae, is placed in a clade of a distinct tribe, Arabideae, and is awaiting future taxonomic revision. Biogeographical evidence suggests an origin of the tribe in Anatolia or adjacent Levant with crown group diversification of the different species starting in the early Pleistocene.The genus Murbeckiella is a suitable system to apply WGS methods to unravel reticulate evolutionary histories of young species complexes. Its small genome allows deep sequencing at high quality, which may facilitate future studies illustrating the genomic footprints and genetic backgrounds of range expansion and transcontinental migration as well as adaptation in rapidly changing alpine environments.
Gesehen am 17.11.2025